On the mechanical behavior of masonry - Sarhosis, Vasilis (2016)
In this chapter, a review on the mechanical behaviour of masonry is presented. The aim is to establish a base of knowledge and understanding of masonry that will underpin its mechanical characteristics and will inform the decisions towards the selection of the computational tool used which are going to be described in the following chapters. Initially, a brief description of the factors that influence the mechanical response of masonry and the variation of the material properties are discussed. The review then considers the possible causes of cracking in masonry and the different failure modes that may occur during loading. Principal findings from the review are summarised at the end of the chapter.